Authority of State Institutions in Establishing Laws Under the Constitution of the Democratic Republic of Timor-Leste - Lourenco de Deus Mau Lulo; I Gusti Ngurah Wairocana; I Wayan Parsa; I Nyoman Suyatna (MultiTech Publisher, 2023)
This dissertation discusses the authority of state institutions in forming laws based on the Constitution of the Democratic Republic of Timor-Leste (RDTL). With regard to the division of powers of state institutions in the 2002 RDTL Constitution, there are many interpretations, because the phrase